Turbidite Outcrops as Analogs for Deep-water Reservoirs: A Case from NW Borneo - S. Back; J.J. Lambiase (Ikatan Ahli Geologi Indonesia, 2001)
Deep-water reservoirs around Borneo are currently an important target for hydrocarbon exploration. Data used to evaluate potential reservoir geometries and quality include quantitative reservoir from outcrop analogs.